Pengaruh Dana Perimbangan dan Kemandirian Keuangan Daerah terhadap Kesejahteraan Masyarakat pada Kabupaten dan Kota di Jawa Barat Tahun 2011 – 2014 - Nugraha, Nugraha; Amelia, Tia (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2017)
The purpose of this study is to determine the effect of intergovernmental transfers fund and the region's autonomy in financing public welfare at local government (municipal and districts) in West Java. This research employs survey with verification approach, and documentation as data collection techniques. Financial data is taken from the report of the budget realization published by the Directorate General of Fiscal Balance (DJPK), the Ministry of Finance of the Republic of Indonesia. The the data of public welfare is taken from the report of human development index (HDI) published by the central agency statistics (BPS) in 2011-2014. The results show that increasing the amount of intergovernmental transfers fund and the level of the region's autonomy in finance have impacts in improving the HDI as a measurement of public welfare